A PSYCHOANALYTIC ANALYSIS OF THE CHARACTER OF THEO FABER IN ALEX MICHAELIDES NOVEL SILENT PATIENT (Journal of Social Sciences Review, 2021)
Abstract:This research study aims to analyze the main character Theo Faber  in the novel "The Silent Patient" written by Alex MichaelIdes through the perspective of Freud's (1923) theory of personality, discussed in his book, The Id and The Ego. Therefore, the researchers have examined the changes in the personality Theo Faber via Id and Ego at different stages. Moreover, this research study has examined the aforementioned character by analyzing it through Id including life (sexual) and death (aggression) instincts, which indicates the impulsive urges of Theo Faber. On the other hand, Ego is used to illustrate the rational decisions and acts of Theo Faber regarding the turmoil he has created due to his Id. Furthermore, the researchers have used qualitative method to get the desired objectives.Keywords: American Id, Ego, Theo Faber , Alex MichaelIdes, Freud's (1923) theory of personality.